The Power of Silence - Ashley, Florence (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2024)
In conversation with Hortense Gallois’ recent essay on the importance of bioethicists participating in public discourse, I suggest that speaking up is as fraught as it is important. Focusing on the anti-trans movement’s misuse of expertise, I highlight the fine line between correcting misinformation and inadvertently causing harm through ill-timed speech. Drawing on the work of Eva Feder Kittay, I suggest that knowing when to speak up and when to stay silent starts with understanding the communities we speak about and the consequences that our words can have on them.